2011
DOI: 10.1246/bcsj.20110224
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-Face Dimeric Tetrathiafulvalenes and Their Cation Radical and Dication Species as Models of Mixed Valence and π-Dimer States

Abstract: Intramolecular interactions of face-to-face tetrathiafulvalenes (TTFs) in 1,8-bis(tetrathiafulvalenyl)naphthalene frameworks were investigated in neutral and cationic states. From X-ray analysis and NMR spectroscopy on neutral 1,8-bis(tetrathiafulvalenyl)naphthalenes, which exist as a mixture of syn-and anti-isomers in solution, there is steric repulsion between TTF moieties. However, analysis of the cyclic voltammogram (CV) revealed that a strong attractive interaction was present in the cation radical state.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 61 publications
2
43
0
Order By: Relevance
“…Hasegawa et al. prepared compounds 26 a – c in which the two TTF units are appended to the naphthalene ring in a face‐to‐face way 39. When the two TTF units were oxidized to TTF ⋅+ in a 1:1 mixture of dichloromethane and acetonitrile, strong intra‐molecular π‐stacking was exhibited for the two TTF ⋅+ units, as evidenced by the appearance of a typical absorption band around 732 nm in the UV/Vis spectrum.…”
Section: Intramolecular Dimerizationsupporting
confidence: 56%
“…Hasegawa et al. prepared compounds 26 a – c in which the two TTF units are appended to the naphthalene ring in a face‐to‐face way 39. When the two TTF units were oxidized to TTF ⋅+ in a 1:1 mixture of dichloromethane and acetonitrile, strong intra‐molecular π‐stacking was exhibited for the two TTF ⋅+ units, as evidenced by the appearance of a typical absorption band around 732 nm in the UV/Vis spectrum.…”
Section: Intramolecular Dimerizationsupporting
confidence: 56%
“…[3] Since then, the p-dimer of oligothiophenes has attracted much attention to elucidate the electronic structure and conduction mechanism of p-doped polythiophenes. [4][5][6][7][8][9][10][11][12][13][14][15] A similar p-dimerization was also observed and studied both experimentally and theoretically in other stable radical-species, such as tetrathiafulvalene (TTF) radical cations, [16] phenalenyl radicals, [17] tetracyanoethylene (TCNE) radical anions, [17c, 18] tetracyanoquinodimethane (TCNQ) radical anions, [18d, 19] and viologen radical cations. [20] Experimental studies conducted thus far on the p-dimers of oligothiophene radical cations have revealed chain-length dependence [5] and solvent effects [6] on p-dimerization in the solution phases and the structures of the p-dimer in crystalline form.…”
Section: Introductionmentioning
confidence: 83%
“…This splitting of the longest absorption band in the spectrum is a typical feature of face‐to‐face arrays of the TTF . + components . As the electronic spectrum of 3Ma 4+ in the diluted solution ( c <10 −5 m ) exhibited almost identical spectral features in these cationic states, the intermolecular π‐dimeric species can be ruled out .…”
Section: Resultsmentioning
confidence: 92%
“…These attractive interactions have been found in many rigid dimeric systems, namely enforced TTF dimers. For an archetypal example of these systems, the cationic TTF dimer 1,8‐bis(tetrathiafulvalenyl)naphthalene 15 n + ( n =1, 2) (Scheme ) shows similar absorption for both the cation radical and dication species: an intensive CR band and remarkable Davydov shift were found as the result of the MV state and π‐dimer formation, respectively . Two cationic TTFs are stacked in face‐to‐face mode with a separation of 3.5–3.7 Å both in 15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation